The relationship between the level of salivary alpha amylase activity and pain severity in patients with symptomatic irreversible pulpitis - Fatemeh Ahmadi-Motamayel; Shahriar Shahriari; Mohammad Taghi Goodarzi; Abbas Moghimbeigi; Mina Jazaeri; Parisa Babaei (Korean Academy of Conservative Dentistry, 2013)
Objectives Assessment of dental pain severity is very challenging in dentistry. Previous studies have suggested that elevated salivary alpha amylase may contribute to increased physical stresses. There is a close association between salivary alpha amylase and plasma norepinephrine under stressful physical conditions. The aim of this study was to evaluate the relationship between pain severity and salivary alpha amylase levels in patients with symptomatic irreversible pulpitis. Materials and Methods Thirty-six patients (20 females and 16 males) with severe tooth pain due to symptomatic irreversible pulpitis were selected. The visual analogue scale (VAS) score was used to assess the pain severity in each patient. Unstimulated whole saliva was collected, and the level of alpha amylase activity was assessed by the spectrophotometric method. Statistical analysis was performed using SPSS 13. Results The level of alpha amylase was significantly increased in the saliva in association with pain severity assessed by VAS. The salivary alpha amylase was also elevated with increased age and in males. Conclusions There was a significant correlation between the VAS pain scale and salivary alpha amylase level, which indicates this biomarker may be a good index for the objective assessment of pain intensity.